2010
DOI: 10.1016/j.foodcont.2010.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Using the Theory of Planned Behaviour to design a food hygiene intervention

Abstract: Twenty percent of food poisoning annually in Australia is believed to result from consumer food handling behaviour. Research advocates the use of social cognition theories in designing food hygiene interventions, however very few studies have actually done so. Thus, this study investigated the efficacy of a food hygiene intervention based on the Theory of Planned Behaviour (TPB). One hundred and eighty-four participants completed a TPB questionnaire, including questions regarding past behaviour and food hygien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 37 publications
1
48
2
3
Order By: Relevance
“…Interestingly, some research tested the effect of past behavior as an additional predictor of the intentions and behavior. For instance, Mullan and Wong (2010) used TPB to predict 33% of intentions and 15% of behavior in a food hygiene intervention; the inclusion of past behavior into the model increased the variance accounted for, respectively of 6% and 4%. Mullan and Wong (2009) also found that TPB explained 66% of variance in intention and 21% in behavior of preparing food hygienically.…”
Section: Research Overviewmentioning
confidence: 99%
“…Interestingly, some research tested the effect of past behavior as an additional predictor of the intentions and behavior. For instance, Mullan and Wong (2010) used TPB to predict 33% of intentions and 15% of behavior in a food hygiene intervention; the inclusion of past behavior into the model increased the variance accounted for, respectively of 6% and 4%. Mullan and Wong (2009) also found that TPB explained 66% of variance in intention and 21% in behavior of preparing food hygienically.…”
Section: Research Overviewmentioning
confidence: 99%
“…Students' sense of invincibility and risky food handling practices may stem from their developmental stage, where asynchronous development of the adolescent brain results in increased risk-taking (Smith et al, 2013) and from psychosocial factors linked to poor food safety behaviours, including low perceived behavioural control (Mullan and Wong, 2010;Mullan et al, 2015), low perceived susceptibility (Haapala and Probart, 2004), and learned habits (i.e., past behaviours; Byrd-Bredbenner et al, 2010;Chow and Mullan, 2010;Haapala and Probart, 2004). Since successfully changing risky food handling behaviours is predicated on feeling susceptible to illness, having incentives to take action, and feeling competent to carry out appropriate actions (Schafer et al, 1993), further research investigating psychological factors and how they can influence students' food safety behaviours is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding author: Shannon E. Majowicz (email: smajowicz@ uwaterloo.ca) college students (Abbot et al, 2012;Byrd-Bredbenner et al, 2008;Milton and Mullan, 2012;Mullan and Wong, 2010;Yarrow et al, 2009). High school students are another potentially important age group to target.…”
Section: Andmentioning
confidence: 99%
“…Ajzen, Fishbein (1980) tarafından geliştirilen PDT modeline göre, niyet, davranışa yönelik tutum ve sübjektif normun yanı sıra algılanan davranışsal kontrolden de etkilenmektedir (Ajzen, 1991;Ajzen, Fishbein, 2008). Algılanan davranışsal kontrol, bireylerin davranışı gerçekleştirmeyi kolay veya zor olarak algılamaları anlamına gelmektedir (Mullan, Wong, 2010). Algılanan davranışsal kontrol, istenilen davranışı gerçekleştirmek için sahip olunan olanaklara yönelik kişinin inancını belirtmektedir (Martin vd., 2011).…”
Section: Planlanmiş Davraniş Teori̇si̇ Modeli̇unclassified
“…Bu sonuç Alam ve Sayuti (2011), Malezya'da bulunan tüketicilerin 'helal' yiyecek satın alma niyetini PDT kapsamında ele aldığı çalışma ile benzerlik göstermektedir. Ancak bu durum literatürdeki bazı çalışmalardan farklılık göstermektedir (Han, Kim, 2010;Han vd., 2010;Alam, Sayuti, 2011;Beaulieu, Godin, 2011;Forward, 2009;Huang vd., 2011;Martini vd., 2011;Mullan, Wong, 2010;Rah vd., 2004;Teo, Lee, 2010;Vela vd., 2010;Baker, White, 2010;Moan, Rise, 2011;Quintal vd., 2010;Sparks, 2007;Erten, 2002). Bu çalışmadaki katılımcıların algılanan davranışsal kontrole ilişkin ifadelere olan yaklaşımları olumludur.…”
Section: Sonuç Ve Tartişmaunclassified